Organizational Readiness to Implement System Changes in an Alaskan Tribal Dental Care Organization. (April 2020) - Randall, C.L.; Hort, K.; Huebner, C.E.; Mallott, E.; Mancl, L.; Milgrom, P.; Nelson, L.; Senturia, K.; Weiner, B.J.; Cunha-Cruz, J.
Introduction: Tribal health care systems are striving to implement internal changes to improve dental care access and delivery and reduce health inequities for American Indian and Alaska Native children. Within similar systems, organizational readiness to implement change has been associated with adoption of system-level changes and affected by organizational factors, including culture, resources, and structure. Objectives: The objectives of this study were to assess organizational readiness to implement changes related to delivery of evidence-based dental care within a tribal health care organization and determine workforce- and perceived work environment–related factors associated with readiness. Methods: A 92-item questionnaire was completed online by 78 employees, including dental providers, dental assistants, and support staff (88% response rate). The questionnaire queried readiness for implementation (Organizational Readiness for Implementing Change), organizational context and resources, workforce issues, organizational functioning, and demographics. Results: Average scores for the change commitment and change efficacy domains (readiness for implementation) were 3.93 (SD = .75) and 3.85 (SD = .80), respectively, where the maximum best score was 5. Perceived quality of management, a facet of organizational functioning, was the only significant predictor of readiness to implement change (B = .727, SE = .181, P < .0002) when all other variables were accounted for. Conclusion: Results suggest that when staff members (including dentists, dental therapists, hygienists, assistants, and support staff) from a tribal health care organization perceive management to be high quality, they are more supportive of organizational changes that promote evidence-based practices. Readiness-for-change scores indicate an organization capable of institutional adoption of new policies and procedures. In this case, use of more effective management strategies may be one of the changes most critical for enhancing institutional behaviors to improve population health and reduce health inequities. Knowledge Transfer Statement: The results of this study can be used by clinicians and other leaders implementing changes within dental care organizations. To promote organizational readiness for change and, ultimately, more expedient and efficient adoption of system-level changes by stakeholders, consideration should be given to organizational functioning generally and quality of management practices specifically.